The effects of product placement, in films, on the consumer's purchase intentions - Barroso, Nuno Alexandre Gaspar da Silva Oliveira (2011)
Traditional forms of communication have been losing their once golden effectiveness due to, mainly, consumer saturation. Since the modern world is characterized by an advertising clutter, in wich each citizen living in urban areas is exposed daily to an average of 3,500 stimuli, companies are now looking for ways to differentiate themselves from competitors, and are now immersing their ways onto product placement. As investment in product placements increases over the years, making it now a billion dollar industry, there is a necessity to deeply explore this theme to better understand what its main effects on consumers are. Purchase intention is a step that mediates consumer attitude and effective behavior. The link between this stage of consumer behavior and product placement represents an area in which previous scholars’ results have not been overly consistent, making it not as crystal clear as desired. The present research conveys an experimental design resorting to eye tracking tools and softwares, providing data concerning the viewers’ levels of attention. As this experiment also aims to denote differences between reactions to product placements in different contexts (comedy vs. drama), two experimental and two control groups were defined, totaling a sample of 85 subjects. This paper covers the effects that the variables identified on the literature review have on brand attitudes, and subsequentely, on purchase intentions. The formulated hypotheses provide an in-depth look to how product placement affects consumers.